Gilt Training for Electronic Sow Feeding Systems in Gestation - C. M. Vier; M. A. Gonçalves; L. L. Thomas; J. C. Woodworth; R. D. Goodband; S. S. Dritz; M. D. Tokach; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2016)
An electronic sow feeding (ESF) system provides the capability of feeding group-housed gestating gilts and sows on an individual basis. One of the most critical and yet often neglected steps in making an ESF system a success is proper gilt training. Different farms have protocols adapted to their particular situation, but the overall goal of gilt training is to ensure that a high percentage of gilts learn how to utilize the ESF station before they are moved to gestation. There are three critical steps in proper gilt training. These include: 1) pre-training; 2) training once the gilts have been moved to the training pen with the ESF; and 3) a post-training period. To have a successful gilt training requires dedicated people who are patient, observant, and also who are able to establish a connection with the females. This frequently necessitates that one or two people are directly responsible for gilt training in an ESF system. This paper will illustrate some of the key gilt training steps involved with an ESF system.
Keywords: electronic sow feeding; gilt training; group-housed gestating sows